Initial combination therapy with metformin plus Colesevelam in drug-naïve hispanic patients with early type 2 diabetes (2012)
Objective: To evaluate initial combination therapy with metformin plus colesevelam in drug-naïve Hispanic patients with type 2 diabetes mellitus. Research Design and Methods: Patients self-identifed as Hispanic from a previous study were included in this exploratory post hoc analysis. Patients were randomized to metformin plus colesevelam or metformin plus placebo. The primary effcacy parameter was the mean change in glycated hemoglobin (HbA1c) levels from baseline. Results: Metformin plus colesevelam had a greater mean HbA1c reduction (-1.2 ± 0.1%) than metformin plus placebo (-0.8 ± 0.1%; P = 0.001) from mean baselines of 7.7% and 7.6%, respectively. Low-density lipoprotein cholesterol (LDL-C), non-high-density lipoprotein cholesterol, total cholesterol, and apolipoprotein (apo) B levels were also reduced (P and lt; 0.0001 for all), while triglyceride (P and lt; 0.0001) and apoA-I (P and lt; 0.05) levels were increased with metformin plus colesevelam treatment compared with metformin plus placebo. With metformin plus colesevelam versus metformin plus placebo, more patients achieved an HbA1c of, 7.0% (75% vs 56%) and LDL-C of, 100 mg/dL (49% vs 14%; both P, 0.05). Conclusion: Metformin plus colesevelam may be an effective initial treatment option for Hispanic patients with early type 2 diabetes mellitus. © Postgraduate Medicine.